ISOLUESHITE: A NEW MINERAL OF THE PEROVSKITE GROUP FROM THE KHIBINA ALKALINE COMPLEX - Chakhmouradian A.; Yakovenchuk V.; Bogdanova A.; Mitchell R.H. (My University, 1997)
Isolueshite, ideally (Na, La, Ca) (Nb, Ti)O3, was found in a hydrothermally altered pegmatite vein in ijolite-urtite of the Khibina alkaline complex, Kola Peninsula, Russia. The host rock consists of microcline, sodalite, aegirine, arfvedsonite and lamprophyllite. Isolueshite occurs as scarce euhedral crystals and their occasional intergrowths enclosed in microcline and sodalite. The crystals reach 0.3 mm in diameter and are a combination of cube and rhombic dodecahedron. The mineral is opaque, optically isotropic, brownish-black in colour; n 2.20(1); some reflectance values are [R, % (λ, nm)]: 16.55 (440), 15,50 (500), 14.80 (560), 14.45 (620), 14.35 (680). Density is 4.72(1)meas., 4.69calc.; VHN70 ranges from 479 to 616. Back-scattered electron imagery revealed a pronounced zonation of isolueshite. The structural formulae calculated from electron microprobe analyses of different zones fall into the following range: (Na0.66-0.73 La0.05-0.08 Ce0.03-0.08 Nd0-0.01 Ca0.05-0.08 Sr0.02-0.03 Th0.01-0.03) (Nb0.52-0.66 Ti0.35-0.49) O3.00. The mineral is cubic (space group Pm3m), a = 3.911(3) Å, Z = 1. The five strongest X-ray diffraction lines are [dmeas. in Å (I) (hkl)]: 3.915 (35) (100), 2.765 (100) (110), 1.953 (53) (200), 1.594 (30) (211), 1.380 (22) (220). The compositional features of isolueshite suggest that the mineral is a stabilised polymorph of NaNbO3. The name is for isometric habit and optical isotropism of the mineral, compared with the orthorhombic polymorph lueshite. Cotype samples are deposited in the Mining Museum of the Mining Institute, St. Petersburg, and in the Mineralogical Museum of St. Petersburg State University, Russia.